19th to early 20th century geology lectures in Saint John, New Brunswick, Canada - Miller, Randy F.; Buhay, Diane N. (Atlantic Geology, 2015)
Saint John, New Brunswick, has a long history of popularization of geology dating back to lectures presented in the 1820s. The first lecture series that included geology and presented to a public audience in 1824 was followed by almost a century of public engagement and presentation of geology topics to a relatively small city of 20 000 to 30 000 people. Lectures were often very general about the science of geology, specific as to the nature of minerals and mining in New Brunswick, and leading edge concerning the first discoveries of significant fossils in the Province. Even though it was a relatively small community, Saint John had an abundance of knowledgeable people, and institutions for presentation and discussion at the Saint John Mechanics’ Institute and the Natural History Society of New Brunswick.